Ultrastructure of young sporophytes of Macrocystis pyrifera (Linnaeus) C. Agardh (Phaeophyceae, Laminariales) - Córdova, César A. (1998)
The anatomical development of young sporophytes of Macrocystis pyrifera obtained from zygotes in laboratory cultures was investigated. Thalli were monostromatic alter two weeks of growth, and cells were similar, photosynthetic, and connected by primary pit fields. Thalli were polystromatic and diferentiated internally into meristoderm, cortex and medulla in the fifth week. Longitudinal sieve filaments appeared in the medulla developing from the inner cortex and they were surrounded by an intercellular matrix. Individual sieve elements contained a nucleus, chloroplasts and several plasmodesmata, which were more or less randomly distributed in transverse walls or they were grouped in primary pit fields in longitudinal walls. Thalli were thicker and diferentiated morphologically into a single lamina, stipe and rhizoidal holdfast alter nine weeks. In addition to sieve filaments, smaller filaments or «hyphae» appeared in the medulla. Possible developmental pathways to adult stages and the relationship of our finding with other studies lor brown algae are discussed.